2015
DOI: 10.1182/blood-2014-08-596734
|View full text |Cite
|
Sign up to set email alerts
|

The histone demethylase Jarid1b is required for hematopoietic stem cell self-renewal in mice

Abstract: Key Points Jarid1b is not required for steady-state hematopoiesis. Jarid1b is required for HSC self-renewal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 18 publications
2
33
0
Order By: Relevance
“…9,10 The function of the other JARID enzymes in the cardiovascular system has not been studied. In this study, we found the enzyme JARID1B, which has been implicated in cell fate decision, cancer progression, and stem cell self-renewal, 5,[11][12][13] to be highly expressed in ECs. By its JmjC domain, JARID1B catalyzes the demethylation of H3K4me2 and H3K4me3.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…9,10 The function of the other JARID enzymes in the cardiovascular system has not been studied. In this study, we found the enzyme JARID1B, which has been implicated in cell fate decision, cancer progression, and stem cell self-renewal, 5,[11][12][13] to be highly expressed in ECs. By its JmjC domain, JARID1B catalyzes the demethylation of H3K4me2 and H3K4me3.…”
mentioning
confidence: 89%
“…14,15 Through this function, JARID1B is involved in the repression of transcription during embryonic development and in embryonic and hematopoietic stem cells. 5,8,11,12,16,17 Therefore, genetic deletion of JARID1B impairs mouse and porcine embryonic development. [18][19][20][21] Considering its effect on gene regulation, we hypothesized that JARID1B affects the expression of endothelial genes and examined the consequences on angiogenesis in human umbilical vein ECs (HUVECs), tamoxifen-inducible conditional, and in the endothelial-specific Jarid1b knockout mouse.…”
mentioning
confidence: 99%
“…4, Table S5C), and a group of multi-functional transcription factors, such as the activators/repressors SP1 and SP2 and development and oncogenesis regulators SRF, SIX5, JunD, c-Myc. JARID1A, an H3K4 demethylase required for haematopoietic stem cell self-renewal, 43,44 showed marginal enrichment in some, but an overall strong depletion, in the majority of aDMRs and aGENs. These results further strengthen the connection of aDMRs and aGENs with the binding of Polycomb repressive complex 2 in the absence of activating transcription factors.…”
Section: Rna Polymerase II and Other Transcription Initiation Factorsmentioning
confidence: 99%
“…A search of the Oncomine database (59,60) showed that JARID1B is up-regulated in multiple types of leukemia (46). JARID1B is important for hematopoietic stem cell renewal (47,48) and is overex- pressed in acute myeloid leukemia. Our data demonstrated a strong increase in expression of JARID1B in B-ALL as compared with normal bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular inhibition of JARID1B using siRNA has shown that JARID1B is important for hematopoietic stem cell renewal (47,48). Here, we tested the effect of pharmacological inhibition of JARID1B on the proliferation of leukemia cells.…”
Section: Inhibition Of Ck2 Restores Ikaros-mediated Repression Of Jarmentioning
confidence: 99%